O direito como arte: a perspectiva de sua expressão autopoiética enquanto ato de criatividade para a organização e decisão: uma forma original a partir da assimetria e da dissolução do ato representativo - Stumpf, Mousés (Universidade do Vale do Rio dos Sinos, 2010)
Law as art in its creative expression, in the dissolution of the world representational models, reinserts Law in the Law itself as form of original expression. As a rupture state, it describes the overcoming of a space marked by the Absolute. In the sense of deparadoxization of the mimetic formula, being such esthetic marked by the symmetry, that searches in the copy the proper self reproduction of the world from deterministic concepts. As an art expression, Law dissolves the ontological model breaching stylizing spaces based on the copy of the nature. In the perspective of the creation of an original workmanship, the esthetic artistic is observed as the space opened for the autopoiesis of the Law system. Such moment describes the phases of the social system evolution as art of the society, in the observation of the creative capacity of the systems in being able to create new antisymmetrical forms subject to give sense to the "admirable new world" that opens itself as complexity. Law as art is the expression of the original form operating its autopoiesis as act of creativity to organize and decide the new, harmonizing, thus, the asymmetry of the world from a manifest workmanship in the art of the society
Keywords: Direito e arte; Filosofia do direito; Autopoiese; ACCNPQ::Ciências Sociais Aplicadas::Direito